การเติบโต ผลผลิตและคุณภาพหลังการเก็บเกี่ยวของกล้วยไม้ตัดดอกพันธุ์ริชชี่ เรด และพันธุ์สิรินทร์คลาสสิค - อริสา วันทัศน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Growth, yield and postharvest quality of 2 year-old cut flower orchid ‘Richy Red’ and ‘Sirin Classic’ were investigated during rainy (August - October 2014) and dry (February – April 2015) seasons. The results showed that the number of new pseudobulb of both cultivars was not significant difference between two seasons. However, the increase of pseudobulb height of ‘Richy Red’ was significantly higher during rainy season than those of dry season while there was no significant difference in ‘Sirin Classic’. Productivity in term of the inflorescence number per plant was higher during dry season consistent with higher maximum photosynthetic rate than during the rainy season. In addition, the inflorescences of ‘Sirin Classic’ showed longer vase life during dry season when compared to those of the rainy season in parallel with higher percentage of flower bud opening while ‘Richy Red’ had no significant difference between these two seasons. The quality of open flower showed no significant difference between two seasons in the both cultivars. These results suggested that both cultivars had high productivity during the dry season and ‘Sirin Classic’ inflorescences had longer vase life and greater bud opening during the dry season as well.